2012
DOI: 10.2147/jpr.s34019
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin administration reduces inflammatory pain in rats

Abstract: In view of the broad range of effects attributed to melatonin, this study evaluated its analgesic effect on inflammatory pain induced by complete Freund’s adjuvant (CFA) in Wistar rats. Inflammation was induced by intradermal CFA injection in the hind paw of all animals, which were then divided into two groups that received either 60 mg/kg of melatonin or vehicle (1% alcohol in saline), intraperitoneally, for three days. The analgesic effect of melatonin was assessed by the hot-plate test, immediately and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In addition, melatonin improves wound healing in pinealectomized animals [38]. Melatonin also reduces pain in rodents [39,40,41,42] due to a direct action on the opiatergic centers in the central nervous system [20,40]. In the present study, the normal daily variation in melatonin was restored 1 day after the surgery, suggesting that this is the time required to initiate the healing processes that follows the surgery.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, melatonin improves wound healing in pinealectomized animals [38]. Melatonin also reduces pain in rodents [39,40,41,42] due to a direct action on the opiatergic centers in the central nervous system [20,40]. In the present study, the normal daily variation in melatonin was restored 1 day after the surgery, suggesting that this is the time required to initiate the healing processes that follows the surgery.…”
Section: Discussionsupporting
confidence: 55%
“…Melatonin was shown to inhibit inflammatory and neurogenic pain by impairing the local production of pain mediators or by inducing the release of endogenous endorphins [18,19,20]. Some clinical studies designed to test melatonin as an analgesic confirmed its effect in reducing pain and morphine consumption [20,21,22,23], while others concluded that melatonin ameliorates anxiety; however, the analgesic effect requires further investigation [24]. Theoretically, if the reduction in nocturnal melatonin is relevant to mounting an innate immune response, the administration of melatonin as a premedication could interfere with the healing process.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the study protocol, we have previously observed antinociceptive effects of melatonin in hot plate and Von Frey tests using the same protocol [16,17] and therefore chose these experimental models to test the effect of melatonin administration on BDNF levels. In addition, the melatonin doses chosen in the present study are in agreement with previous studies showing that the anti-inflammatory effects of melatonin starting at 10 mg/kg are less evident than those observed at lower doses [27], and with other studies showing an analgesic effect at higher doses [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were randomly allocated to one of two groups (n = 7-8 per group): melatonin (treatment) or vehicle (control). Rats in the melatonin group were treated with intraperitoneal injections of melatonin (60 mg/kg, final solution 60 mg/ml), while those in the control group received vehicle (1% ethanol in saline) [16,18,19]. Treatment was administered 1 h after CFA injection and once daily for the subsequent 48 h (for a total of 3 days of melatonin administration), always at 3.00 p.m.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation